Optimization of Traffic Public Education by Kamsel Unit in Preventing Traffic Accidents in the Jurisdiction of the Demak Police - Almaasah, Noor Fajar (Advances in Police Science Research Journal, 2024)
Traffic public education carried out by the kamsel unit of the Demak Police traffic unit has the aim of creating security, safety, order, and smooth traffic and minimizing traffic accidents by providing education and knowledge to the public. Currently, the awareness of people of Demak Regency to drive securely and safely of driving remins low, so the accident rate is still high. In order to overcome the existing problems, the Demak Police kamsel unit seeks to optimize the dikmas lantas which is guided by the Guidelines for the Implementation of the Chief of Police No. Pol: Juklak / 05 / V / 2003 concerning Traffic Civil Education. The focus of this research was optimization of civil education kamsel unit preventing traffic accidents by taking data on traffic accidents for the past five years in Demak Regency. In this research, researchers used management theory and SWOT theory, also used the concept of public education, the concept of security and safety units, and the concept of traffic accidents as an analysis knife to discuss research findings problems, and their solving efforts. This research used a qualitative approach with the type of field research. The source of the data was obtained from Demak Police personnel and several publics through interviews, observations and documents in the Demak Police. The validity of the data can be proven by using data triangulation. Meanwhile, data analysis techniques was carried out by reducing data, presenting data, and drawing conclusions. Some of the findings obtained by the researchers were: The schedule on the activity plan is not in accordance with the implementation, The entire personnel of the kamsel unit ranging from kanit to banit have not been carried out dikjur or prolat, there are a lot of materials that should have been updated, facilities and infrastructure still have to be maintained regularly. Based on the findings, there is still a need for optimization in the kamsel unit and the author will provide alternative problems solving to the findings obtained. So that through civil education carried out by the kamsel satlantas unit of the Demak Police in preventing traffic accidents, it can be carried out optimally and the kamseltibcar lantas can then be realized.